Assessment of additional relative plaque removing efficacy of a newly available toothbrush - D S Kalsi; Kulmeet Kaur; Amanpreet Singh; Vikrant Sharma; Naveen Oberoi; Aanchal Sood (Wolters Kluwer Medknow Publications, 2018)
Aim: To confirm claimed additional efficacy of Sensodyne Expert tooth brush over other commonly used commercially available tooth brushes. Methods and Materials: This was a single use randomized double blind study for the assessment of plaque remaining after tooth brushing with Sensodyne Expert tooth brush to that remaining after brushing with the. Forty subjects were enrolled in the study. Only the right-handed subjects were chosen for the study. One side of the subjects' oral cavity was randomly assigned to be brushed with Sensodyne Expert toothbrush while the other was brushed using the already in use subject's regular tooth brush for one minute each side. Two tone disclosing agent was then used to identify and score post-brushing plaque remaining after tooth brushing on the selected teeth. Plaque was scored using the Turesky et al. Modified Quigley-Hein Plaque Index (TQHPI) on selected teeth on both sides of the oral cavity. Results: The mean post brushing plaque score for assessed teeth brushed with Sensodyne Expert tooth brush was 1.283 ± 0.39, while that with already in use subject's regular tooth brush was and 1.153±0.71. Student t-test was used for analysis of results. There was an nonsignificant difference in post brushing plaque scores of both groups at assessed p value (P = 0.078). This suggests that subjects of this study were able to equally effectively remove plaque using their own and Sensodyne Expert tooth brushes. Conclusion: The plaque removing efficacy of Sensodyne Expert tooth brush was comparable to that of other tooth brusheswhen plaque on the selected teeth remaining after tooth brushing was assessed. Additional plaque removing efficacy of Sensodyne Expert tooth brushover subjects' other already in use toothbrushes was not found.